Some new deterministic and random variational inequalities and their applications. (1995) - Yuan, Xian-Zhi; Roy, Jean-Marc
Abstract : A non-compact deterministic variational inequality which is used to prove an existence theorem for saddle points in the setting of topological vector spaces and a random variational inequality. The latter result is then applied to obtain the random version of the Fan's best approximation theorem. Several random fixed point theorems are obtained as applications of the random best approximation theorem.